2022
DOI: 10.3390/molecules27207123
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Antilymphoma Activity of Annona macroprophyllata Donn and Its Acyclic Terpenoids: In Vivo, In Vitro, and In Silico Studies

Abstract: Annona macroprophyllata Donn (A. macroprophyllata) is used in traditional Mexican medicine for the treatment of cancer, diabetes, inflammation, and pain. In this work, we evaluated the antitumor activity of three acyclic terpenoids obtained from A. macroprophyllata to assess their potential as antilymphoma agents. We identified the terpenoids farnesyl acetate (FA), phytol (PT) and geranylgeraniol (Gg) using gas chromatography–mass spectroscopy (GC-MS) and spectroscopic (1H, and 13C NMR) methods applied to petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 51 publications
(99 reference statements)
0
0
0
Order By: Relevance
“…Several researchers have explored ilama leaves as a source of antihyperglycemiants and anticancer agents. It has been reported that ilama leaves contain flavonoid glycosides, sesquiterpenoids and an aliphatic compound [2,6].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several researchers have explored ilama leaves as a source of antihyperglycemiants and anticancer agents. It has been reported that ilama leaves contain flavonoid glycosides, sesquiterpenoids and an aliphatic compound [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the antitumoral properties, as inductors of apoptosis, of Gg and PT may be mediated by the generation of ROS. Once the induction of late apoptosis was demonstrated by the acyclic terpenoids Gg, PT, and FA, we evaluated their capability of inducing the production of ROS in the U-937 cells, considering that the production of ROS in physiologic and pathological cases may be associated with the induction of apoptosis [6]. The results showed that the terpenoids Gg and PT induced a significant increase in ROS production, with values of 58.7 and 31.5% (Table 1) of the mean fluorescence shift (Figure 3E,F).…”
Section: Effect Of Geranylgeraniol Phytol and Farnesyl Acetate Isolat...mentioning
confidence: 99%
See 3 more Smart Citations